Uso de geotecnologias para avaliação de áreas aptas à disposição final de resíduos sólidos urbanos na Bacia hidrográfica do Rio dos Sinos - Folletto, Flávio Aguiar (Universidade do Vale do Rio dos Sinos, 2016)
Faced with modern patterns of development and consumption, equating the management of solid urban waste (MSW) has become a major challenge not only for public administration, but also for society. The final disposal of solid urban waste demands constant expansion of the operating systems, in response to the growing population increase and consequent increase in the daily quantity of waste generated. National laws recommend economic and social development, allied to environmental quality. Based on this premise, evaluating locational alternatives for activities and enterprises have become important tools to analyze possible environmental integrity risks. One example is the demand for landfill sites, which implies meeting multiple economic, social and environmental criteria. In this situation, the present study intends, through the geotechnologies, to identify suitable areas for final disposal of MSW in the Rio dos Sinos River Basin. In addition, it is intended to evaluate the possibility of cooperative management (public consortiums) between the municipalities of the same Hydrographic Basin. During the development of this study, digital data inherent to environmental, social and economic bases, together with those related to Environmental Licensing in the State of Rio Grande do Sul, formed a group of factors limiting the implantation of sanitary landfills, scripted and worked in a Geographic Information System (GIS). In addition to the digital data available in governmental and private entities, cartographic bases were created in the absence of information. From the organization of these databases, thematic maps were generated considering the restrictive criteria, approached for this study. In a second stage, the evaluation recommended the possibility of shared management of the resulting areas, visualizing arrangements between the municipalities. Finally, the proposed methodology set out an analysis of ground truthing through high resolution images, considering the elements of the landscape and the effectiveness of the systematics developed, besides confirming the effectiveness of this proposal, discussing its applicability to other management units. The results drives to 26 areas, unequally distributed by the Rio dos Sinos River Basin, due to physical and environmental characteristics. From this total, 7 areas presented an effective opportunity of management consortium between the municipalities components of the management unit, fully meeting the proposed parameters for the study. In addition, the selected areas, when submitted to the evaluation of the components of the landscape in larger scales, demonstrate the effectiveness and applicability of the proposal. The replication of the method proved to be tangible to other regions, reflecting the importance of past evaluations of engineering works for sanitary landfills, reducing costs and reducing environmental impacts.
Keywords: Geotecnologias; Resíduos sólidos urbanos; Aterro sanitário; Geotechnology; Solid urban waste; Landfill; ACCNPQ::Engenharias::Engenharia Civil